Consumer purchase intention towards organic food in Selangor, Malaysia/ Aslinda Mohd Shahril, Chemah Tamby Chik and Nurul Hanis Amer - Mohd Shahril, Aslinda; Tamby Chik, Chemah; Amer, Nurul Hanis (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
The consumption of organic food products is proliferating among consumers worldwide. However, in Malaysia, organic food consumption among Malaysian is still at a low level. Limited studies were found to investigate the factors on customer purchase intention to organic food. This study aimed to examine the factors that influence consumer purchase intention and consumption of organic food. This study used the quantitative method, and questionnaires were distributed to 140 respondents in Subang Jaya, Petaling Jaya, and Shah Alam, Malaysia. The results were then analysed using SPSS, and it was found that attitude, subjective norms, and health consciousness have a significant positive relationship with customer purchase intention to organic food. Next, the limitation, recommendations, and implications of the study were suggested for future research.